Influence of different Eucalyptus hybrids on soil macrofauna - Gomes, Vanessa S.; Barreto-Garcia, Patrícia A B; Scoriza, Rafael N.; Júnior, Valdemiro C.; Pereira, Jhuly E S; Fernandes, Jamily S. (FapUNIFESP (SciELO), 2022)
The present work aimed to evaluate the influence of different eucalyptus hybrids on the edaphic macrofauna community. It is hypothesized that the density and diversity of edaphic fauna are influenced by the quantity and quality of the litter deposited by the different hybrids on the soil surface. The study area is in the city of Vitória da Conquista (BA) and consists of seven eucalyptus hybrids, one from sexual reproduction (seminal) and six from asexual (clonal) reproduction. Sampling of the soil macrofauna was performed by the Tropical Soil Biology and Fertility method. All visible invertebrates were collected and identified at the level of large taxonomic groups. The relative density, group richness, and diversity index were calculated. Hybrids did not influence the total density and richness of the soil macrofauna. However, it was possible to observe changes in litter accumulation and composition, and as a result in the diversity indexes and in the presence or absence of macrofauna groups. Among the studied hybrids, those from Eucalyptus urophylla (seminal, 1335 and 1249) promote greater macrofauna diversity and favor the occurrence of detritivores organisms, suggesting the occurrence of better quality and more palatable litter for the edaphic fauna.